Electrocardiogram interpretation competency among emergency nurses and emergency medical service (EMS) personnel: A cross‐sectional and comparative descriptive study. Issue 4 (21st February 2021) - Rahimpour, Maryam; Shahbazi, Shahla; Ghafourifard, Mansour; Gilani, Neda; Breen, Cathal
Abstract: Aims: The aim of this research study was to compare electrocardiogram (ECG) interpretation competency among emergency nurses and EMS personnel. Design: A cross‐sectional comparative descriptive study design was used. Methods: This study recruited 170 participants (105 emergency nurses and 65 EMS personnel) in northwest of Iran. Data were collected during 2018 using ECG, an interpretation competency questionnaire and analysed using SPSS V.24 through independent t test, linear regression, Pearson and Spearman correlation coefficient. A statistical significance of p < .05 was assumed. Results: The study results showed a mean score of 6.65 ± 2.16 out of 10 for emergency nurses' and 4.87 ± 1.81 for EMS personnel ECG interpretation competency ( p < .05). Conclusions: Hospital emergency nurses were more qualified to interpret the ECG than the pre‐hospital emergency medical personnel ( p = .792 and β (SE)) = 0.22 (0.84). Active involvement in ECG interpretation and standard continued education are needed to develop and improve the emergency nurses and EMS personnel ECG interpretation competency.